Oxygen Toxicity and the Superoxide Dismutase - Gregory, Eugene M. (1973)
Oxygen caused an increase in the amount of superoxide dismutase in Escherichia coli B but not in Bacillus subtilis. E. coli B cells, induced by growth under 100% O(2), were much more resistant to the lethal effects of 20 atm of O(2) than were cells which contained the low uninduced level of this enzyme. In contrast, B. subtilis, which could not respond to O(2) by increasing its content of superoxide dismutase, remained equally sensitive to hyperbaric O(2) whether grown under 100% O(2) or areobically. The catalase in these organisms exhibited a reciprocal response to oxygen. Thus, the catalase of E. coli B was not induced by O(2), whereas that of B. subtilis was so induced. These results are consistent with the view that superoxide dismutase is an important component of the defenses of these organisms against the toxicity of oxygen, whereas their catalases are of secondary importance in this respect. The ability of streptonigrin to generate O(2)(−), by a cycle of reduction followed by spontaneous reoxidation, has been verified in vitro. It is further observed that E. coli B which contain the high induced level of superoxide dismutase were more resistant to the lethality of this antibiotic, in the presence of oxygen, than were E. coli B which contained the low uninduced level of this enzyme. This difference between induced and uninduced cells was eliminated by the removal of O(2). These results are consistent with the proposal that the enhanced lethality of streptonigrin under aerobic conditions may relate to its in vivo generation of O(2)(−) by a cycle of reduction and spontaneous reoxidation. In toto, these observations lend support to the hypothesis that O(2)(−) is an important agent of oxygen toxicity and that superoxide dismutase functions to blunt the threat posed by this reactive radical.